Phytoremediaton of priority substances (Pb and Ni) by Phragmites australis exposed to poultry slaughterhouse wastewater - Topal, Murat; Topal, E. Isil Arslan (Taylor & Francis Inc, 2020)
The aim of the work was to evaluate the ability of Phragmites australis to uptake lead and nickel from the stream taking the treated poultry slaughterhouse wastewater (PSW). Pb and Ni concentrations, which are the priority substances of the water frame directive, were detected separately at the root, stem and leaf of P. australis at 50 m and 100 m from the downstream of discharge point. The uptake of Pb and Ni by P. australis followed the order of root > leaf > stem. The Ni uptake was higher than Pb uptake in P. australis exposed to poultry wastewater. As a result, P. australis exposed to PSW were found to have the ability to uptake Pb and Ni. It has been determined that P. australis can be used for removal and phytoremediation of Pb and Ni metals from PSWs.
Keywords: Lead; nickel; Phragmites australis; plant uptake; poultry; wastewater